The Methodology of Suhayb Al-Saqqar in Critiquing the Thought of Muhammad Shahrur on the Issue of the Clear (Muhkam) and the Ambiguous (Mutashabih) in the Glorious Quran - BasimTaha Abdullah; Muhammad Hadi Shihaba (Islamic Sciences Journal, 2025)
In his critique of Shahrur's view of synonymy, Al-Saqqar explains that Shahrur denied the existence of synonymy in the Arabic language and the Glorious Quran, which contradicts the positions of the linguistic and legal heritage. Al-Saqqar believes that synonymy was a linguistic research issue within the heritage, and was not a subject of controversy as in the contemporary reading proposed by Shahrur. Al-Saqqar believes that Shahrur's denial of synonymy leads to the presentation of a new and confused conception of Islam. In this research, the researcher adopted the descriptive approach to analyze Muhammad Shahrur's contemporary reading of the issue under study. He also followed this descriptive approach in presenting Suhaib Al-Saqqar's critique of that reading. He then employed the analytical approach to establish a critical methodology for the contemporary reading of the Glorious Quran.